Iraq Crude Oil Exports – October, November, December/ 2024 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2025)
Table 1. Iraq Crude Oil Exports – October 2024 Table 2. Iraq Crude Oil Exports – November 2024 Table 3. Iraq Crude Oil Exports – December 2024